2020
DOI: 10.4314/ahs.v20i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma homocysteine and blood pressure in hypertensive Northern-Nigerians

Abstract: Aim: The study sought to determine whether there is any relationship between plasma homocysteine and blood pressure levels in Nigerians with essential hypertension. Method: It was a cross-sectional analytical study done on 120 randomly selected hypertensive patients and 120 normal healthy controls seen at the large Conference hall of the Ahmadu Bello University (ABU) Medical Centre, Zaria as well as the ABU Teaching Hospital, Zaria, Northern-Nigeria. Pearson’s Correlation and Binary Logistic Regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…The Hcy level in group B exhibited a negative correlation (r = -0.309, p = 0.029) with blood pressure (both diastolic and systolic). In contrast, Onyemelukwe et al (27) observed that Hcy is positively correlated to blood pressure (systolic and diastolic). The disparity in ethnic group and population size may account for the various findings.…”
Section: Discussionmentioning
confidence: 88%
“…The Hcy level in group B exhibited a negative correlation (r = -0.309, p = 0.029) with blood pressure (both diastolic and systolic). In contrast, Onyemelukwe et al (27) observed that Hcy is positively correlated to blood pressure (systolic and diastolic). The disparity in ethnic group and population size may account for the various findings.…”
Section: Discussionmentioning
confidence: 88%
“…При изучении ФР инсульта получено, что артериальная гипертензия достоверно чаще встречалась среди носителей полиморфизма MTRR A66G. Исследования, посвященные влиянию носительства полиморфизма MTRR A66G на развитие артериальной гипертензии, ранее не проводились, но есть данные, свидетельствующие о повышении уровня артериального давления при увеличении концентрации гомоцистеина [18][19][20][21]. Патогенез этого объясняется тем, что гомоцистеин способен ингибировать фермент NO-синтетазу, а это уменьшает биодоступность оксида азота [22][23][24].…”
Section: показатели коагулограммы в группах сравненияunclassified
“…The next group of papers is in the NCDs realm: obesity 28 , 29 , 30 , diabetes 31 , 32 , 33 , 34 , acute kidney injury 35 plasma homocysteine and hypertension 36 , coronary care 37 and cancer 38 , 39 . Then we have papers on smoking and lung function 40 , epilepsy 41 , and gall stones 42 .…”
mentioning
confidence: 99%